Etika Pengentasan Kemiskinan: Studi Komparasi Pemikiran Ibnu Taimiyah dan Mahatma Gandhi - Arsyadani, Achmad Arfinanto; Rofiah, Khusniati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This article discusses a comparative perspective of Ibn Taimiyah and Mahatma Gandhi regarding the ethics of poverty alleviation. Despite coming from different religious and cultural backgrounds, both figures offer profound insights into economic equality and social justice, as well as an ethical framework for addressing poverty. Ibn Taimiyah emphasizes the importance of wealth management based on Islamic principles, while Gandhi highlights simplicity, self-reliance, and the fair distribution of resources in line with the philosophy of ahimsa (non-violence). This article aims to formulate a practical approach to the ethics of poverty alleviation based on the thoughts of these two figures